Factor analysis approach to classify COVID-19 datasets in several regions - Mohammad Reza Mahmoudi (Results in Physics, 2021)
The aim of this research is to investigate the relationships between the counts of cases with Covid-19 and the deaths due to it in seven countries that are severely affected from this pandemic disease. First, the Pearson’s correlation is used to determine the relationships among these countries. Then, the factor analysis is applied to categorize these countries based on their relationships.